Effect of organic and inorganic sources of nutrients on secondary and micronutrient content in rice at various growth periods - Puli, Mohana Rao; Prasad, PRK; Ravindra Babu, P; Narasimha Rao, KL; Subbaiah, G (ORYZA-An International Journal of Rice, 2019)
A field experiment was conducted on fine texture soils to find out the effect of different sources of nutrients on secondary (Ca and Mg) and micro nutrient (Fe, Mn, Cu and Zn) content in rice at various growth periods. The experiment was laid out in a randomized block design in kharif season with four treatments and replicated five times. The treatments consisted of M1 (RDF - Control), M2 (10 t FYM ha-1 + RDF), M3 (1.5 t vermicompost ha-1 + RDF), M4 (Green manuring + RDF). The nutrient content in rice at various growth periods was significantly increased with the application of 100 % NPK in combination with FYM @ 10 t ha-1. However, it was on par with that of green manuring together with 100 % NPK during both the years of the study.